Wayne School of Engineering: Case Study of a Rural Inclusive STEM‐Focused High School. (October 2014) - Peters Burton, Erin; Kaminsky, Samuel E.; Lynch, Sharon; Behrend, Tara; Han, Edmund; Ross, Kathleen; House, Ann
<x xml:space="preserve">Abstract</x> Rural schools face challenges that are often different than nonrural schools. Resource constraints are particularly acute in rural schools, and they struggle to offer advanced courses and extracurricular programs. The purpose of this paper is to present a descriptive, instrumental case study of an inclusive rural science, technology, engineering, and mathematics school that has successfully dealt with challenges and offers an innovative and productive learning environment, despite limited resources. For this study, a variety of on‐site and off‐site data collection techniques were used such as focus groups, classroom observation protocols, and surveys. Wayne School of Engineering (WSE) overcomes resource barriers by matching their schedule to the local community college, upgrading the rigor of their high school classes and facilitating student transition to college. WSE also requires extracurricular research projects that help students see the relevance of their in class learning, build 21st century skills, and connect to partners outside of the school. Faced with limited budgetary, technological, and logistical resources, WSE administrators, teachers, and students work collectively to overcome these barriers and provide high‐quality education by finding ways to blur the lines of traditional secondary schools.